PENGARUH RATA-RATA LAMA SEKOLAH, UMUR HARAPAN HIDUP DAN PENGELUARAN PER KAPITA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI ACEH - Nurjihan Amanda Sikumbang; Nur Hayati; Asnidar Asnidar; Puti Andiny; Safuridar Safuridar; Nurlaila Hanum (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study analyzes the effect of average years of schooling, life expectancy, and per capita expenditure on economic growth in Aceh Province for the period 2010–2024 using multiple linear regression. The results show that average years of schooling has a negative and significant effect, indicating that improvements in education have not been able to directly drive economic growth. Life expectancy has a negative but insignificant effect, suggesting that better health conditions have not yet contributed optimally to increasing economic output. In contrast, per capita expenditure has a positive and significant effect, indicating that higher purchasing power plays a stronger role in stimulating economic activity.